Antigen processing and immune regulation in the response to tumours. Issue 1 (12th October 2016) - Reeves, Emma; James, Edward
Summary: The MHC class I and II antigen processing and presentation pathways display peptides to circulating CD8 + cytotoxic and CD4 + helper T cells respectively to enable pathogens and transformed cells to be identified. Once detected, T cells become activated and either directly kill the infected / transformed cells (CD8 + cytotoxic T lymphocytes) or orchestrate the activation of the adaptive immune response (CD4 + T cells). The immune surveillance of transformed/tumour cells drives alteration of the antigen processing and presentation pathways to evade detection and hence the immune response. Evasion of the immune response is a significant event tumour development and considered one of the hallmarks of cancer. To avoid immune recognition, tumours employ a multitude of strategies with most resulting in a down‐regulation of the MHC class I expression at the cell surface, significantly impairing the ability of CD8 + cytotoxic T lymphocytes to recognize the tumour. Alteration of the expression of key players in antigen processing not only affects MHC class I expression but also significantly alters the repertoire of peptides being presented. These modified peptide repertoires may serve to further reduce the presentation of tumour‐specific/associated antigenic epitopes to aid immune evasion and tumour progression. Here we review the modifications to the antigen processing and presentation pathway in tumours and how it affects the anti‐tumour immune response, considering the role of tumour‐infiltrating cell populations and highlighting possible future therapeutic targets. Abstract : Antigen processing and presentation is essential for the recognition of tumours by the immune system. The tumour however, modulates the pathway to prevent its detection and clearance.